Massively parallel microbubble nano-assembly - Joh, Hyungmok; Lian, Bin; Hsueh, Shaw-iong; Ma, Zhichao; Lee, Keng-Jung; Zheng, Si-Yang; Fischer, Peer; Fan, Donglei Emma (Nature Communications, 2025)
Microbubbles are an important tool due to their unique mechanical, acoustic, and dynamical properties. Yet, it remains challenging to generate microbubbles quickly in a parallel, biocompatible, and controlled manner. Here, we present an opto-electrochemical method that combines precise light-based projection with low-energy electrolysis, realizing defined microbubble patterns that in turn trigger assembly processes. The size of the bubbles can be controlled from a few to over hundred micrometers with a spatial accuracy of ~2 μm. The minimum required light intensity is only ~0.1 W/cm2, several orders of magnitude lower compared to other light-enabled methods. We demonstrate the assembly of prescribed patterns of 40-nm nanocrystals, 200 nm extracellular vesicles, polymer nanospheres, and live bacteria. We show how nanosensor-bacterial-cell arrays can be formed for spectroscopic profiling of metabolites and antibiotic response of bacterial assemblies. The combination of a photoconductor with electrochemical techniques enables low-energy, low-temperature bubble generation, advantageous for large-scale, one-shot patterning of diverse particles in a biocompatible manner. The microbubble-platform is highly versatile and promises new opportunities in nanorobotics, nanomanufacturing, high-throughput bioassays, single cell omics, bioseparation, and drug screening and discovery.